Faktor Keprilakuan yang Mempengaruhi Keandalan Informasi Laporan Keuangan - Putu Ayu Diah Widari Putri; Nyoman Yudha Astriayu Widyari; Ida Ayu Komang Tiara Pratistha Sari (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The reliability of financial reporting information is an important aspect in maintaining the credibility of financial institutions, especially Rural Banks (BPR) that operate based on public trust. This study aims to analyze the influence of organizational commitment, individual integrity, ethical orientation, and external pressure on the reliability of financial reporting information at BPRs in Bali Province. This study used a quantitative approach with a purposive sampling technique, involving 75 respondents from 10 BPRs who met the criteria of length of service and involvement in the financial reporting process. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS. The results showed that organizational commitment, individual integrity, and ethical orientation had a significant positive effect, while external pressure had a negative but insignificant effect on the reliability of financial reporting information. These findings emphasize the importance of strengthening ethical values ​​and employee integrity in strengthening the reliability of financial reporting, while also supporting the application of Agency Theory which emphasizes the importance of controlling agent behavior to align with the interests of the principal. This study provides practical implications for BPR management to strengthen organizational culture and ethical oversight as part of the internal control system.